Sol–gel synthesis and characterisation of La doped (1−x)BaTiO3–x(Bi0·5K0·5)TiO3 PTCR ceramics. (May 2015) - Zhang, C.; Di, L. Z.; Ding, C. H.; Lu, L. X.; Zhai, T.; Yang, D. A.
<x content-type="archive" xml:space="preserve">Abstract</x> As a promising material for lead free positive temperature coefficient of resistivity (PTCR) ceramics, La doped (1−x)BaTiO3–x(Bi0·5K0·5)TiO3 [(1−x)BT–xBKT] samples with 0≤x≤0·04 were prepared by a citrate–nitrate sol–gel method. The corresponding gels were heated at different temperatures (500, 600 and 800°C) to study the conditions necessary for the formation of the pure BT–BKT. Single phased perovskite powders with average particles size of 70 nm were obtained by heating the precursor gels at 800°C for 1 h in air. The crystal structure, microstructure and the electrical properties of La doped BT–BKT samples were studied. When the content of La was 0·2 mol.-%, the 0·99BT–0·01BKT ceramic showed the lowest ρRT. With increasing addition of BKT, the Curie temperature (Tc) and the room temperature resistivity (ρRT) increased. When the content of BKT was 4 mol.-%, the sample sintered in air atmosphere still showed good PTCR behaviours with Tc = 143°C, ρRT = 1·1×104 Ω cm and lg (ρmax/ρmin) = 3·76.